THE APPLICATION SCOPE OF COMPREHENSIVE QUALITY STANDARDS IN FIELD OF ADMINISTRATIVE ORGANIZATION AND ACADEMIC PROGRAM IN COLLEGES OF BASIC EDUCATION IN DOHUK UNIVERSITY. - Sadeeq, Siyar Tamar (Journal of Duhok University, 2018)
The present research aims at measuring the application scope of comprehensive quality standards in field of administrative organization and academic program in colleges of basic education in Dohuk University. The research is depended on descriptive analytical approach and a sample consists of 26 administrators were chosen for the present study. In order to achieve the goals of the study, the researcher has prepared a tool in terms of comprehensive quality standards and the final formula of the tool was consisted of 55 items distributed over two axes. After applying the tool and collecting information, the result showed that comprehensive quality standards among samples of research in fields of administrative organization and academic program were not function in field of administrative organization, while it was in field of academic organization. The result also showed that there are no differences of functional statistical in both fields according to geographical location variable ( Dohuk-Akri). Finally, the researcher has submitted a number of recommendations suggestions relevant to the study topic.